Pathways of Continuity: Indonesia’s Role in Southeast Asia’s Refugee Governance - Prabandari, Atin; Ketaren, Emma Seruni; Segara, Balya Arung (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2025)
This article interrogates the enduring character of non-binding, sovereignty-centric refugee governance across Southeast Asia by analyzing the role of Indonesia within two principal displacement episodes: the Indochinese refugee crisis (1975–1996) and the ongoing Rohingya crisis. Applying the analytical lens of historical institutionalism and foregrounding the notion of path dependency, the account demonstrates how operational norms forged under the Comprehensive Plan of Action—including temporary humanitarian shelter, conditional burden redistribution, and the construal of displacement as a temporary aberration—have resurfaced in Indonesia’s present-day posture. Archival records, policy tracts, and a selective review of the secondary literature furnish a reconstruction of Jakarta’s stewardship of the Galang Island camp and an assessment of its recent practices toward the Rohingya, encompassing semi-offshore rescues and deference to international humanitarian actors. The inquiry substantiates profound institutional and normative continuities that circumscribe Indonesia’s capacity and readiness to construct durable, rights-respecting protection frameworks, notwithstanding a shifting geopolitical and humanitarian tableau. By embedding Indonesia’s trajectory within the regional governance matrix, the study illuminates historical legacies that continue to inform Southeast Asian refugee policy and underscores the constraints afflicting reactive, episodic cooperation in the face of protracted displacement. Keywords: Indochinese refugee, Indonesia, refugee crisis, refugee governance, Rohingya refugee, Southeast Asia